Letter (copy) - Tewson, Vincent
1938-07-01 038-0134-001 Secretary's. HVT/FC/EK/1436. 1st July, 1938. Mr. H. MacCullum Scott, The Basque Children's Committee, 4, Great Smith Street, London, S.W.1. Dear Mr. Scott, I am returning the copy of the letter for insertion in "Truth" which you sent with your letter of the 30th June. I agree to my name being appended. Yours sincerely, Assistant Secretary. Letter. 292/946/38/134(I)